(3GdceGd aj GdaQhSjI hCfhGY GdSdGM hBOGH GdYed HPdc hUaGJ GdSjha hGdQeGMs ((3LGfe ef CRHc s)
(3ChdgG (B:s
(3HYO GdHSedI (B: (3GHJOGA GdQchH hJYdje GdaQhSjI , GdMeO ddg Pi GdYXeI hGdSWGf GdeJYGdi HGdbOQg s
(3BNQgG (B:s
(3HGH GdYed HWYf GdeRQGb s
(3fSNI NRGFfjI HQSe GdSdWGf CHj GdfUQ bGfUhg GdZhQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeY (B- (3U (B33 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs